Evaluation of sanitation facilities in relation to communicable diseases in government primary schools in Mkinga District Council - Mosha, Irene V (Mzumbe University, 2026)
A dissertation submitted to the School of Public Administration and Management in partial fulfilment of the requirements for award of the degree of Masters of Science in Health Monitoring and Evaluation (MSc. HME) of Mzumbe University